Suppression of glutathione system and upregulation of caspase 3-dependent apoptosis mediate rohypnol-induced gastric injury - R. E. Akhigbe; D. T. Oluwole; T. E. Adegoke; M. A. Hamed; D. C. Anyogu; A. F. Ajayi (Taylor & Francis Group, 2022)
Objectives: This study investigated the impact of rohypnol on gastric tissue integrity.Methods: Forty male Wistar rats were randomized into control, low dose rohypnol-treated, high dose rohypnol-treated, low dose rohypnol-treated recovery and high dose rohypnol-treated recovery groups.Results: Rohypnol caused significant rise in gastric malondialdehyde (MDA), oxidized glutathione (GSSG), nitric oxide (NO), tumour necrotic factor-α (TNF-α), and interleukin-6 (IL-6) levels. Also, rohypnol caused reductions in gastric reduced glutathione (GSH) (as well as GSH/GSSG), and activities of superoxide dismutase (SOD), catalase, glutathione-S-transferase (GST), glutathione peroxidase (GPx), cyclo-oxygenase (COX-2). Furthermore, rohypnol upregulated caspase 3 activity and induced gastric DNA damage, evident by a rise in 8-hydroxydeoxyguanosine (8-OHdG) and DNA fragmentation index (DFI) in gastric tissue. These alterations were coupled with reduced gastric weight and distorted gastric cytoarchitecture. Cessation of rohypnol caused a significant but not complete reversal of rohypnol-induced gastric damage.Conclusion: This study revealed that rohypnol induced gastric injury by suppressing glutathione content and COX-2 activity, and upregulating caspase 3-dependent apoptosis, which was partly reversed by rohypnol withdrawal.